2005
DOI: 10.1111/j.1365-2141.2005.05534.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in multiple myeloma – possibility or probability?

Abstract: SummaryIn a small number of patients with multiple myeloma (MM), long-term disease-free survival has been achieved by harnessing the immune phenomenon, 'graft-versus-tumour' effect, induced by allogeneic haemopoietic stem cell transplantation. This has prompted many investigators to examine ways in which a patient's own immune system can be more effectively directed against their disease, with the ultimate aim of tumour eradication. In this review we assess the current understanding of immunobiology in MM, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 169 publications
(142 reference statements)
0
29
0
Order By: Relevance
“…In addition, it has been shown that long-term disease control can be achieved in a subset of MM patients after allo-SCT [71]. However, important challenges remain, as allo-SCT in MM is still associated with a relatively high relapse rate that could be explained by the immune suppressive phenotype of residual MM cells [8]. Moreover, the use of allo-SCT in MM also represents a certain risk of GvHD and transplantrelated mortality, despite the use of RIC regimens.…”
Section: Allogeneic Transplantation In MM Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it has been shown that long-term disease control can be achieved in a subset of MM patients after allo-SCT [71]. However, important challenges remain, as allo-SCT in MM is still associated with a relatively high relapse rate that could be explained by the immune suppressive phenotype of residual MM cells [8]. Moreover, the use of allo-SCT in MM also represents a certain risk of GvHD and transplantrelated mortality, despite the use of RIC regimens.…”
Section: Allogeneic Transplantation In MM Patientsmentioning
confidence: 99%
“…Both the number and the activity of several immune effector cells (Fig. 1) are affected by immune suppression in MM and this partially explains the anti-neoplastic activity of non-cellular immunotherapies, such as immunomodulatory drugs, which are able to revert immune effectors to their physiological functions [7][8][9][10][11][12].…”
Section: Immune Cell Alterations In Multiple Myelomamentioning
confidence: 99%
See 1 more Smart Citation
“…As a proof of principle, recombinant MV that has been blinded for usage of CD46 and/or CD150 by site-specific mutagenesis within the H protein sequence has been rescued successfully, as have recombinants retargeted for usage of carcinoembryonic antigen or CD38 by fusion of the H protein open reading frame with that of the respective single-chain antibody (scFv) (Nakamura & Russell, 2004;Parato et al, 2005). For multiple myeloma (MM) cells in particular, several candidate surface antigens including MUC-1, sperm protein 17 and differentiation antigens such as CD38 and CD138 have been evaluated for targeted therapy, although with limited success to date (Greiner et al, 2000a;Treon et al, 2000;Harrison & Cook, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative approaches are clearly needed to prolong the disease-free survival as well as the overall survival of patients with MM. To prolong the survival of patients with MM who are undergoing allogeneic HSCT, donor lymphocyte infusion can be used successfully as a salvage therapy, which is based on the graft-versus myeloma effect in some cases of MM that relapse after allogeneic HSCT (Harrison & Cook, 2005;Perez-Simon et al, 2003). This role of immune effector cells provides the framework for the development of immune-based therapeutic options that use antigen-presenting cells (APCs) with increased potency, such as dendritic cells (DCs), in MM (Harrison & Cook, 2005).…”
Section: Introductionmentioning
confidence: 99%